The State, the Dialogue and the Transformation Process of Socio-environmental Conflicts - Castro, Augusto (2020)
This article discusses the necessary linkages that must exist between the State and the dialogue. To propose that the State is the space for dialogue par excellence, the text relies on the ethical nature that is inherent in the constitution of the State. Furthermore, the State represents a strategic and forward-looking perspective for human life in the world that is expressed and founded on such important issues as equality, recognition and democracy. This reflection about the State aims to reposition the role of the State in the face of its actual difficulties and limitations at becoming a true space for dialogue. The article reviews the characteristics that any dialogue must have taking into account the characteristics of conflicts, and especially socio-environmental ones, and their transformation process. It insists on the role of openness, open communication and permanent negotiation that the State must play to face the challenges posed by society and the environment. Finally, the article seeks to review ideas and concepts related to dialogue, redefine criteria and raise the need to build capacities and public policies to adequately face the challenges and conflicts that may arise.